-4x+10=-3(2x+2)

Simple and best practice solution for -4x+10=-3(2x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4x+10=-3(2x+2) equation:


Simplifying
-4x + 10 = -3(2x + 2)

Reorder the terms:
10 + -4x = -3(2x + 2)

Reorder the terms:
10 + -4x = -3(2 + 2x)
10 + -4x = (2 * -3 + 2x * -3)
10 + -4x = (-6 + -6x)

Solving
10 + -4x = -6 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
10 + -4x + 6x = -6 + -6x + 6x

Combine like terms: -4x + 6x = 2x
10 + 2x = -6 + -6x + 6x

Combine like terms: -6x + 6x = 0
10 + 2x = -6 + 0
10 + 2x = -6

Add '-10' to each side of the equation.
10 + -10 + 2x = -6 + -10

Combine like terms: 10 + -10 = 0
0 + 2x = -6 + -10
2x = -6 + -10

Combine like terms: -6 + -10 = -16
2x = -16

Divide each side by '2'.
x = -8

Simplifying
x = -8

See similar equations:

| 660/x=25/3 | | 0.4(x-4)=4.0 | | (x-3+9i)(x-3-9i)=0 | | 3y+8x=12 | | X*.03=28 | | 1/5(3x-4)=2/5 | | 1-x+4x+17=3x | | h([-3])=2x+4 | | y=0+(-4) | | 6x^2+12x=4 | | 4=-y | | 2x+6=8x-31 | | .85=200 | | 3x-12+15=2x+10 | | 5y-9+y+36=8y+30-5y | | 0.8=200 | | 13x+7=5x+7 | | 4(lnx)-lnx^4=0 | | 7x+8=7x+3 | | 0.25=10 | | 5x+3=-3+3x+22 | | x+7x+4+2x=30+4 | | 2x-17=11-5x | | x+x=x+222 | | 5a^2-5a+1=0 | | (3x+2z)(2x-7z)= | | 33-3x=12x | | y=6(x-1)+9 | | 9x+4=12x+6 | | 3x(x+4)=18 | | 4x-12+16=3x+12 | | 3c+4n=12 |

Equations solver categories